(untitled) (Sinología hispánica. China Studies Review, 2025)
The Spanish Jesuit Adriano de las Cortes left in the Philippines in 1629 a lavishly illustrated chronicle titled Journey to China. While the main body of the work records many natural and humanistic landscapes of late Ming Dynasty Canton, it is the process of capture, interrogation and escort in 1625-1626 that appears to be the primary purpose of the writing, and the reasons why he travelled and quickly wrote the text seem to be more profound. Starting from three philological details, i.e. the unusual season of departure, the unskilled references to Chinese officials, and apparent hostility from the local people, this paper combines relevant historical facts and materials to reveal that de las Cortes came well prepared for the trip instead of “common” shipwreck. This suggests his journey was likely in response to the Dutch presence and competition in Canton and Hokkien region during the first three decades of the 17th century.